Combined Constant‐Force and Constant‐Velocity Single‐Molecule Force Spectroscopy of the Conrotatory Ring Opening Reaction of Benzocyclobutene. Issue 11 (27th July 2016) - Kouznetsova, Tatiana B.; Wang, Junpeng; Craig, Stephen L.
Abstract: Single‐molecule force spectroscopy (SMFS) of multi‐mechanophore polymers has been used to provide kinetic and mechanistic insights into mechanochemical reactions. Whereas biological systems have benefitted from force clamp spectroscopy, synthetic polymers have been studied primarily with constant‐velocity methods. Here, force clamp SMFS is applied to the mechanically accelerated conrotatory ring opening of benzocyclobutene, and a comparison with constant‐velocity SMFS extends the range of available rate‐versus‐force data and corroborates the use of constant‐velocity SMFS to extract force dependencies. Abstract : Kinetics extracted from force clamp and constant‐velocity single‐molecule force spectroscopy experiments provide a consistent picture of the rate of a conrotatory ring opening reaction as a function of applied force.